Immunoglobulin heavy chain gene rearrangement in heavy chain deposition disease suggests it is a plasma cell disease: a case report. Issue 3 (March 2022) - Rao, Qingqing; Xu, Ricong; Wan, Qijun
Heavy chain deposition disease (HCDD) is characterized by the deposition of truncated monoclonal immunoglobulin heavy chains along glomerular basement membranes. Truncated heavy chains are thought to be associated with plasma cell disease (PCD), but previous bone marrow cytology tests showed that only 30% of HCDD cases are related to PCDs. We report the first known use of immunoglobulin heavy chain (IGH) gene rearrangement to diagnose a patient with γ3-HCDD, although bone marrow morphology test identified no abnormalities. Our findings provide strong evidence for a correlation between PCDs and HCDD, which could help understand the genetic background underlying abnormal heavy chains and assess disease prognosis. Further, concordant with previous findings, bortezomib-based chemotherapy had a good therapeutic effect in our patient. We summarize the experience of diagnosing and treating a case of HCDD, and combine this with a literature review to further explore the correlation between PCDs and HCDD, which has important clinical value.